Two Episodes of Ventriculoperitoneal Shunt Migration in a Patient with Idiopathic Intracranial Hypertension. (19th February 2014) - Balakrishnan, V.; Jeanmonod, R.
Abstract : Introduction . Ventriculoperitoneal shunts are often placed as treatment for refractory idiopathic intracranial hypertension. Dislodgement and migration of the distal portion of the shunt are more common in obese patients and can be difficult to detect. We report the case of a woman with two separate episodes of shunt migration into her abdominal wall. Case Presentation . We report a case of a 37-year-old female with history of obesity eventually diagnosed with idiopathic intracranial hypertension (IIH) as the cause. She failed outpatient therapy and, through neurosurgery, had a VP shunt placed for symptom control. She had subsequent development of worsened symptoms that were found to be due to shunt migration. This happened not once but twice to the same patient. Conclusion . Shunt dislodgement, migration, and subsequent failure are common in obese patients who have shunts placed for IIH. The medical provider should maintain a high index of suspicion for shunt malfunction in these patients, particularly because clinical evaluation may be challenging due to habitus.